“What huge influence they could have !” : Consumer empowerment in and around Quebec’s first Consumer Protection Act - Le Guerrier, Catherine (Les Cahiers de droit, 2022)
This paper explores the figure of the empowered, and enlightened consumer, who is capable of inflecting the production and commercial processes to reflect his ideals, as it appears in the debates surrounding the adoption of Quebec’s first Consumer Protection Act in 1971. It shows that this ideal was defended strongly by groups who were, paradoxically, quick to criticize consumers’ inability to distinguish their wants from their needs. These groups also advocated many protection measures that were seemingly identical to those put forward by groups who imagined the consumer to be a much humbler figure. After reviewing the socioeconomic changes that led to the adoption of the law, I explore these paradoxes in light of the history and objectives of two consumer advocacy groups, the CAC and the FACEF. I suggest that the latter, the boldest of the two, had a coherent view of the consumer. However, the figure of the greater-than-life consumer was only one part of a much larger project of emancipation ; in the FACEF’s view, it could never have effectiveness as a mere legal concept.